Application of Water Quality Index (WQI) to Assess Suitability of Water from Different Sources for Human Consumption in Hong Local Government Area, Adamawa State, Nigeria - Jefferson, Geoffrey; Shingu, Elisha Daniel (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study evaluates the quality of water from various sources—stream, borehole, and well—in the Hong metropolitan area of Hong Local Government, Adamawa State, using the Water Quality Index (WQI) technique. The objective is to determine the suitability of these water sources for human consumption and domestic use by computing WQI values based on key physico-chemical parameters. Water samples were collected from multiple locations and analyzed for pH, total alkalinity, total hardness, calcium, magnesium, electrical conductivity, dissolved oxygen, biochemical oxygen demand, total dissolved solids, and total suspended solids. The WQI values varied across sampling sites, reflecting spatial differences in water quality. Findings indicate that borehole water samples consistently fall within acceptable WQI ranges, confirming their suitability for drinking and domestic purposes. In contrast, stream water samples exhibited poor WQI ratings, rendering them unsafe for human consumption. The study concludes that while borehole water presents a reliable source of potable water in the region, stream water requires treatment before use. These results underscore the importance of regular water quality monitoring to inform safe water resource management in rural and peri-urban areas.